Gratitude and Grace: The Writings of Michael Mayne - Huffstetler, Joel W. (Hamilton Books, 2009)
Gratitude and Grace: The Writings of Michael Mayne offers an introduction and overview of the five bestselling books by one of the United Kingdom's finest spiritual writers, Michael Mayne, who served as dean of Westminster Abbey from 1986 to 1996. Previously, he had served as vicar of Great St. Mary's (the University Church), Cambridge, and as Head of Religious Programmes for BBC Radio. Mayne's primary vocation was that of pastor, not writer, but his deep pastoral wisdom shines through in his books. Though clearly Christian in orientation, Michael Mayne's books were written to appeal to all who are on a quest to integrate spirituality into their daily lives. His work recalls the very best of English pastoral writing, such as that of George Herbert, Thomas Traherne, and Francis Kilvert. The list of the finest English pastoral books now includes those by Michael Mayne (d. 2006). Gratitude and Grace: The Writings of Michael Mayne is the first book-length treatment of Mayne's writings and will remain the starting point of Mayne studies for years to come.